Optimized rapid thermal process for high efficiency silicon solar cells - Noël, S; Slaoui, A; Peters, S; Lautenschlager, H; Schindler, R; Muller, J.C (Solar energy materials and solar cells, 2001)
Rapid thermal processing is opening new possibilities for a low-cost and environmentally safe silicon solar cell production, keeping the process time at high temperature in the order of 1 min, due to enhanced diffusion and oxidation mechanisms. Controlling the surface concentration of the junction is one of the major parameters, in order to obtain suitable front surface recombination velocities. Simultaneous diffusion of phosphorus and aluminum is used to realize emitter and back surface field in a single high-temperature step, with optimized gettering effect. Controlling the mentioned parameters on industrial 1 Ω cm Cz material lead in 17.5% efficient solar cells on a surface of 25 cm 2. All results are discussed in terms of process temperature, dopant source concentration and effective process time, below 1 min including high heating and cooling rates.